2020
DOI: 10.3390/su12020679
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Can the Green Belts Prevent Urban Sprawl?—A Comparative Study of Frankfurt am Main, London and Seoul

Abstract: A salient issue facing contemporary urban development in many countries is that the physical areas of major cities are growing at a faster rate than their populations. The popularity of the green belt concept among advocates is that it can effectively counter urban sprawl while safeguarding the countryside from urban development. This paper is intended to measure the efficacy of the green belt in preventing urban sprawl through an international comparative study in three cities of different sizes, and which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 17 publications
0
8
0
7
Order By: Relevance
“…Green belts have been parts of cities all over the world for years ( Pieck, 2019 , Svensson et al, 2020 ). An interesting conclusion by Xie et al (2020b) should be mentioned here that there is apparently no proof of the popular belief that strict implementation of green belts as urban development tools can prevent urban sprawl.…”
Section: Discussionmentioning
confidence: 94%
“…Green belts have been parts of cities all over the world for years ( Pieck, 2019 , Svensson et al, 2020 ). An interesting conclusion by Xie et al (2020b) should be mentioned here that there is apparently no proof of the popular belief that strict implementation of green belts as urban development tools can prevent urban sprawl.…”
Section: Discussionmentioning
confidence: 94%
“…The current trend is that green areas are recognized worldwide as providing amenities to urban residents and bringing positive effects to surrounding properties. Its importance has also increased in recent years, playing a positive and important role in helping people physically and emotionally in overcoming the Covid-19 outbreak [27][28][29][39][40][41][42][43][44]. However, when a greenbelt is established, the people most affected by it are the landowners and officials within the greenbelt that are directly regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization, which causes population growth, negatively affects greenbelts due to the construction of urban infrastructure and pressure on the urban ecosystem [39]. On the other hand, it is not clear whether greenbelts have successfully prevented urban sprawl at a regional level or within urban centers [40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For examples, several authors have revealed that green belts in cities play diverse roles in promoting urban sustainability by enhancing the aesthetics of urban landscape [30,52]; providing space for relaxation [52,53], leisure and recreation [24]; and serving as watershed, wetlands and agricultural lands for food production [44]. They also help in curbing urban sprawl and urban amalgamation [54], serving as sources of medicinal plants and food trees [25,55]. Green belts are also known to protect natural areas, clean water, fresh air and wildlife, provide natural habitats for plants and animals [15], help in air pollution control and storm water management [18][19][20]56]; reduction in energy consumption in buildings [20,57]; and in carbon dioxide sequestration [23,58].…”
Section: Greenbelts and Urban Development Agendamentioning
confidence: 99%